Interpersonal Communication Strategies for Conflict Management and Relationship Maintenance in Lesbian Couples - Vionita Wijaya; Zera Edenzwo Subandi; Teguh Hidayatul Rachmad (Universitas Tribhuwana Tungga Dewi, 2025)
This study aims to examine how lesbian couples manage conflict through interpersonal communication by analyzing the strategies they use to maintain healthy relationships between them. The approach used is a qualitative case study based on Relationship Rules Theory. The data was gathered over a period of two months through semi-structured interviews, observations, and field notes, capturing both verbal and non-verbal cues. The informants included two lesbian couples, along with insights from a close friend and a relationship counselor. Findings indicate that successful conflict management often depends on open and honest dialogue, willingness to compromise, and a deep understanding of each partner's emotional needs and values. Many couples emphasize the importance of creating a safe space for vulnerability, where both partners feel heard and respected. Additionally, external challenges—such as discrimination or lack of family support—sometimes influence how conflicts are handled, requiring couples to develop additional resilience. By highlighting these communication dynamics, this study contributes to a deeper understanding of how lesbian couples maintain their relationships despite facing social barriers. This research also provides practical insights for relationship counselors, educators, and LGBTQ+ advocates who wish to support healthy conflict resolution in same-sex relationships.Penelitian ini bertujuan untuk menganalisis bagaimana pasangan lesbian mengelola konflik melalui komunikasi interpersonal dengan menganalisis strategi yang mereka gunakan untuk mempertahankan hubungan yang sehat di antara mereka. Pendekatan yang digunakan adalah studi kasus kualitatif berdasarkan Teori Aturan Hubungan. Data dikumpulkan selama dua bulan melalui wawancara semi-terstruktur, observasi, dan catatan lapangan, yang menangkap isyarat verbal dan non-verbal. Informan yang terlibat terdiri dari dua pasangan lesbian, bersama dengan wawasan dari seorang teman dekat dan seorang konselor hubungan. Temuan menunjukkan bahwa pengelolaan konflik yang sukses seringkali bergantung pada dialog yang terbuka dan jujur, kesediaan untuk berkompromi, serta pemahaman yang mendalam tentang kebutuhan emosional dan nilai-nilai masing-masing pasangan. Banyak pasangan menekankan pentingnya menciptakan ruang aman untuk kerentanan, di mana kedua pasangan merasa didengar dan dihormati. Selain itu, tantangan eksternal—seperti diskriminasi atau kurangnya dukungan keluarga—kadang-kadang memengaruhi cara konflik ditangani, sehingga pasangan perlu mengembangkan ketahanan tambahan. Dengan melihat dinamika komunikasi ini, penelitian ini berkontribusi pada pemahaman yang lebih dalam tentang bagaimana pasangan lesbian mempertahankan hubungan mereka meskipun menghadapi hambatan sosial. Penelitian ini juga memberikan wawasan praktis bagi konselor hubungan, pendidik, dan advokat LGBTQ+ yang ingin mendukung resolusi konflik yang sehat dalam hubungan sesama jenis.